Excluding glances: Analysis of the stigmas in the social construction and experience of indigence in Montes de Oca, Costa Rica - Chaves-Chang, Luis Diego (2026)
Most cities in the world suffer from a structural problem of poverty degradation that implies the appearance of homeless individuals. These people, usually called homeless, suffer negative looks from the rest of the population for their mere existence. The stigma they grieve is not harmless but rather generates a painful self-perception that they suffer in their daily lives. In the present study we focus on describing the phenomenon of social stigmatization aided by a theoretical perspective that, assisted by the ethnographic information collected, allows us to describe the stigmas that affect the homeless population and the way in which they see themselves. This work employed, from an anthropological perspective, the use of qualitative techniques among homeless people in San Pedro de Montes de Oca, mainly those involved in the REDESMIDI project of the community’s social pastoral care. Among the results, we observed how failure to comply with the model of a citizen dedicated to work is one of the main determinants that shape the stigma that affects homelessness, and how the incorporation of stigmas by the homeless population also affects their self-perception and social development.